(untitled) (Journal of Engineering, 2005)
The undrained stability of cohesive slopes (0) subjected to surcharge loads is studied in this paper. Problems of this kind are involved in structures rapidly built near the crest of cohesive slopes and heavy equipment (e.g. draglines, buldozers and railways) move on slope. Using the non-linear finite element method, the effects of line loads and uniformly distributed loads are studied and the distribution of stresses under these loads is examined. The value of Per (critical line load) required equating the driving and resisting moments for a unit length of the slope was computed using the computer program. The process was repeated until a mininnum Per was obtained.